A cohort study of the perinatal outcome of radiofrequency ablation in complicated monochorionic multiple pregnancies based on a different needle insert angle. Issue 5 (May 2021) - Liu, Qian; Shi, Xiaomei; Fang, Liyuan; Rao, Tengzi; Shi, Lishuang; Wu, Jing
Objective: To compare the pregnancy outcomes of radiofrequency ablation (RFA) for complicated multiple pregnancies between fetal abdominal and dorsal needle insertion angles. Methods: We performed a historical cohort study of patients who underwent selective reduction using RFA through different needle insertion angles from 2015 to 2018 at a local hospital. Dorsal needle insertion cases were consecutively selected and abdominal needle insertion cases were selectively enrolled. The Cox proportional hazards model was constructed to identify predictors of fetal survival time with different needle insertion angles. Results: The RFA procedure was performed in 28 women through an abdominal insertion angle and in 28 women through a dorsal insertion angle. There were no significant differences in perinatal outcomes between the two groups. The overall live birth rate after RFA in the two groups was 73.5% and the mean gestation was 31.6 ± 6.5 weeks. The Cox model showed that gestational age at RFA was a predictor of the duration of the period between RFA and delivery. Conclusion: RFA conducted through the dorsal insertion angle is technically feasible for selective reduction in complex monochorionic multiple pregnancies. Gestational age at this procedure is an independent risk factor for the duration of pregnancy post-RFA.